1) (8х + 5,2) : 2,4 = 11 : 2 2) 4 : 1,6 = (7х - 2) : 10,4
(8х + 5,2) · 2 = 2,4 · 11 1,6 · (7х - 2) = 4 · 10,4
(8х + 5,2) · 2 = 26,4 1,6 · (7х - 2) = 41,6
8х + 5,2 = 26,4 : 2 7х - 2 = 41,6 : 1,6
8х + 5,2 = 13,2 7х - 2 = 26
8х = 13,2 - 5,2 7х = 26 + 2
8х = 8 7х = 28
х = 8 : 8 х = 28 : 7
х = 1 х = 4
3) (х - 0,2) : 0,8 = 4,2 : 1,2 4) (3х + 0,8) : 9,6 = 4,8 : 3,6
(х - 0,2) · 1,2 = 0,8 · 4,2 (3х + 0,8) · 3,6 = 9,6 · 4,8
(х - 0,2) · 1,2 = 3,36 (3х + 0,8) · 3,6 = 46,08
х - 0,2 = 3,36 : 1,2 3х + 0,8 = 46,08 : 3,6
х - 0,2 = 2,8 3х + 0,8 = 12,8
х = 2,8 + 0,2 3х = 12,8 - 0,8
х = 3 3х = 12
х = 12 : 3
х = 4
5) (5х + 3) : 9 = 27 : 13,5 6) 8 : 20 = 28 : (9х + 7)
(5х + 3) · 13,5 = 9 · 27 8 · (9х + 7) = 20 · 28
(5х + 3) · 13,5 = 243 8 · (9х + 7) = 560
5х + 3 = 243 : 13,5 9х + 7 = 560 : 8
5х + 3 = 18 9х + 7 = 70
5х = 18 - 3 9х = 70 - 7
5х = 15 9х = 63
х = 15 : 5 х = 63 : 9
х = 3 х = 7
Пошаговое объяснение:
х^4 -а^4 +а^3 •х-ах^3 +с^3 •х-ас^3=
Решаем по действиям:
х^4 -а^4=(х-а)(х+а)(х^2 +а^2)
а^3 •х-ах^3=ах(а^2 -х^2)=ах(а-х)(а+х)=-ах(х-а)(х+а)
с^3 •х-ас^3=с^3(х-а)
Итог:
(х-а)(х+а)(х^2 +а^2)-ах(х-а)(х+а)+с^3(х-а)=(х-а)((х+а)(х^2 +а^2-ах)+с^3)=(х-а)(х^3 +а^3 +с^3)
а^3 -а^2 +х^3 -х^2 +а^2 х+ах^2=(a^3 +а^2 х)-(а^2 +х^2)+(х^3 +ах^2)=а^2(а+х)+х^2(а+х)-(а^2 +х^2)=(а+х)(а^2 +х^2)-(а^2 +х^2)=(а^2 +х^2)(а+х-1)
(х^3 +у^3)+(ху^2 +х^2 у)+(х^2 z+y^2 z)=(x+y)(x^2 -xy+y^2)+xy(x+y)+z(x^2 +y^2)=(x+y)(x^2 -xy+xy+y^2)+z(x^2 +y^2)=(x+y)(x^2 +y^2)+z(x^2 +y^2)=(x+y+z)(x^2 +y^2)
a^3 +a+ab^2 -a^2 b-b-b^3=(а^3 -a^2 b)+(a-b)+(ab^2 -b^3)
Решаем по действиям:
a^3 -a^2 b=a^2(a-b)
ab^2 -b^3=b^2(a-b)
Итог:
(a-b)(a^2 +1+b^2)
(3а^3 +12а^2)-(а+4)=3а^2 (а+4)-(а+4)=(3а^2 -1)(а+4)
(а^3 +а^2)+(а+1)=а^2(а+1)+(а+1)=(а^2 +1)(а+1)
(az^2 +az)-(bz^2 +bz)-(a-b)=az(z+1)-bz(z+1)-(a-b)=(z+1)(az-bz)-(a-b)=(z+1)z(a-b)-(a-b)=(a-b)(z+1)(z-1)=(a-b)(z^2 -1)
3*6=18
3*7=21
3*8=24
3*9=27
3*10=30
3*11=33
3*12=36
3*14=42
3*15=45
3*16=48
3*17=51
3*18=54
И так далее